BENEFIT SHARING MODEL EXPERIMENTED BY TROPICAL BOTANIC GARDEN AND RESEARCH INSTITUTE (TBGRI), A NATIONAL CENTER OF EXCELLENCE ON TROPICAL PLANT DIVERSITY, MINISTRY OF ENVIRONMENT & FORESTS, GOVERNMENT OF INDIA
A lead provided by a tribal community, Kani tribe, inhabiting the Southern- Western Ghat region of Kerala State in India, relating to the anti-fatigue properties of a wild plant Trichopus zeylanicus has led to bioprospecting and development of a scientifically validated drug “Jeevni” by the Tropical Botanic Garden and Research Institute (TBGRI). The TBGRI in consultation with the tribal community has worked out an arrangement for benefit sharing. According to this arrangement, the TBGRI has agreed to share 50% of the licence fee and royalty with the tribal community.